Pemanfaatan Realitas Buatan (Augmented Reality) dalam Inovasi Teknousaha untuk Meningkatkan Pengalaman Konsumen di Era Digital - Ramadhan, Muhammad Firly; Lukman Abdurrahman (IPM2KPE, 2026)
This study aims to analyze the use of Augmented Reality (AR) in techno-entrepreneurship to enhance consumer experience in the digital era. The research method used was a literature review, collecting and analyzing scientific literature, industry reports, and case studies related to the application of AR in various business sectors. The results show that AR can enhance visual and emotional interactions among consumers, provide interactive product and service simulations, strengthen brand engagement, and improve the efficiency of purchasing decision-making. The study concludes that the integration of AR in techno-entrepreneurship provides significant added value for consumers, strengthens loyalty, and is an effective digital innovation strategy for enriching the customer experience. Keywords: Augmented Reality, Techno-entrepreneurship, Consumer Experience, Digital Innovation